Assessing Latin American neoliberalism: Introduction to a Debate - Weyland, Kurt
The present set of Research Notes, which were first presented at a forum on Latin America's market reforms held at the 2003 Latin America Studies Asociation Congress, investigates the economic and social repercussions of the neoliberal ware that swpt across the region during the 199s